ANALYSIS OF THE AIR OF THE WORKING AREA AT ENTERPRISES OF THE CONSTRUCTION INDUSTRY THE IN PROCESS OF WELDING AND THERMAL SLIT - Vasilii Ivanovich Gumenyuk; Oksana Sergeevna Vlasova; Natalia Sergeevna Zhukova (Современная наука и инновации)
The article discusses the emissions of hazardous substances into the working area in different parts of the production process of the construction and engineering industries depending on the method of welding and sawing of metal.